JURIDICAL STUDY ON THE CONCEPT OF JUDICIAL PARDON AND VICTIM PROTECTION IN JUVENILE CASES: ANALYSIS OF DECISION NUMBER 2/PID.SUS-ANAK/2021/PN RGT - Rani Adriana; Nurini Aprilianda; Sriti Hesti Astiti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Abstract